2020
DOI: 10.1111/eve.13272
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a vaginal septum in a foal diagnosed with pyometra

Abstract: Summary A 10‐week‐old Westphalian filly was presented for vaginal discharge of 14‐days' duration. Examination revealed a partial vaginal septum and pyometra. Two Group B streptococcal pathogens (Streptococcus dysgalactiae subspecies equisimilis and Streptococcus equi subspecies zooepidemicus) were isolated from the uterus. Pyometra was successfully treated using endoscopically facilitated removal of intraluminal exudate and locally and systemically administered antimicrobials. The filly was reported to be prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…angular limb deformities, wry‐nose, cleft palate); or in some cases, such as that presented by McCarthy et al . (2021), are present from birth, are only detected later in life.…”
Section: Disorders Of Sexual Development (Dsd)mentioning
confidence: 99%
See 4 more Smart Citations
“…angular limb deformities, wry‐nose, cleft palate); or in some cases, such as that presented by McCarthy et al . (2021), are present from birth, are only detected later in life.…”
Section: Disorders Of Sexual Development (Dsd)mentioning
confidence: 99%
“…Reflecting on the report by McCarthy et al . (2021), there was no record of the gonadal status of the filly involved and karyotyping was not performed. Given that we have suggested that vaginal septal remnants may have formed as a failure of the wall between the two paramesonephric ducts to dissolve one should consider whether cervical and uterine abnormalities are also present.…”
Section: Abnormalities By Regionmentioning
confidence: 99%
See 3 more Smart Citations